The chimera of S1 and N proteins of SARS-CoV-2: can it be a potential vaccine candidate for COVID-19?. (3rd August 2022) - Kumar, Amresh; Ladha, Amit; Choudhury, Ankita; Ikbal, Abu Md Ashif; Bhattacharjee, Bedanta; Das, Tanmay; Gupta, Gaurav; Sharma, Chhavi; Sarbajna, Adity; Mandal, Subhash C; Choudhury, Manabendra Dutta; Ali, Nahid; et al.
ABSTRACT: Introduction: Coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has emerged as one of the biggest global health issues. Spike protein (S) and nucleoprotein (N), the major immunogenic components of SARS-CoV-2, have been shown to be involved in the attachment and replication of the virus inside the host cell. Areas covered: Several investigations have shown that the SARS-CoV-2 nucleoprotein can elicit a cell-mediated immune response capable of regulating viral replication and lowering viral burden. However, the development of an effective vaccine that can stop the transmission of SARS-CoV-2 remains a matter of concern. Literature was retrieved using the keywords COVID-19 vaccine, role of nucleoprotein as vaccine candidate, spike protein, nucleoprotein immune responses against SARS-CoV-2, and chimera vaccine in PubMed, Google Scholar, and Google. Expert opinion: We have focussed on the use of chimera protein, consisting of N and S-1 protein components of SARS-CoV-2, as a potential vaccine candidate. This may act as a polyvalent mixed recombinant protein vaccine to elicit a strong T and B cell immune response, which will be capable of neutralizing the wild and mutated variants of SARS-CoV-2, and also restricting its attachment, replication, and budding in the host cell.